Childhood Maltreatment, Educational Attainment, and IQ: Findings From a Multicentric Case-control Study of First-episode Psychosis (EU-GEI). (9th February 2022) - Sideli, Lucia; Schimmenti, Adriano; La Barbera, Daniele; La Cascia, Caterina; Ferraro, Laura; Aas, Monica; Alameda, Luis; Velthorst, Eva; Fisher, Helen L; Caretti, Vincenzo; Trotta, Giulia; Tripoli, Giada; et al.
Abstract: Background and hypothesis: Evidence suggests that childhood maltreatment (ie, childhood abuse and childhood neglect) affects educational attainment and cognition. However, the association between childhood maltreatment and Intelligence Quotient (IQ) seems stronger among controls compared to people with psychosis. We hypothesised that: the association between childhood maltreatment and poor cognition would be stronger among community controls than among people with first-episode of psychosis (FEP); compared to abuse, neglect would show stronger associations with educational attainment and cognition; the association between childhood maltreatment and IQ would be partially accounted for by other risk factors; and the association between childhood maltreatment, educational attainment, and IQ would be stronger among patients with affective psychoses compared to those with nonaffective psychoses. Study Design: 829 patients with FEP and 1283 community controls from 16 EU-GEI sites were assessed for child maltreatment, education attainment, and IQ. Study Results: In both the FEP and control group, childhood maltreatment was associated with lower educational attainment. The association between childhood maltreatment and lower IQ was robust to adjustment for confounders only among controls. Whereas childhood neglect was consistently associated with lower attainment and IQ in both groups, childhood abuse was associated with IQ only in controls. Among both patients with affective and nonaffective psychoses, negative associations between childhood maltreatment and educational attainment were observed, but the crude association with IQ was only evident in affective psychoses. Conclusions: Our findings underscore the role of childhood maltreatment in shaping academic outcomes and cognition of people with FEP as well as controls.